PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE MAKE A MATCH DI KELAS V SDN 12 TANAH SIRAH KOTA PADANG - Kurnia Putri, Melani; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low academic performance of fifth-grade students at SD Negeri 12 Tanah Sirah, Padang City, which was caused by difficulties in understanding Pancasila Education topics, low curiosity, and limited student participation in a learning process that remained teacher-centered. This research aimed to explain the improvement of students’ learning outcomes in Pancasila Education through the implementation of the Cooperative Learning model of the Make a Match type. The research method employed was Classroom Action Research (CAR) using qualitative and quantitative approaches, conducted in two cycles consisting of planning, implementation, observation, and reflection. The findings indicated that the average score of teaching module implementation increased from 89.58% (good) in Cycle I to 95.83% (very good) in Cycle II. The teacher’s instructional implementation aspect improved from 89.77% to 97.22%, and student activity also increased from 89.77% to 97.22%. The average student learning outcome in Cycle I was 72.10 (fair), consisting of attitude (71.03), knowledge (75.50), and skills (69.78). In Cycle II, learning outcomes improved with average scores of 87.07 for attitude, 91.50 for knowledge, and 86.24 for skills, resulting in an overall average of 88.27 (good). In conclusion, the Cooperative Learning Make a Match model is proven to be effective in improving students’ learning outcomes in Pancasila Education for fifth-grade students at SD Negeri 12 Tanah Sirah, Padang City.